Realism Dominance in Indonesia’s Security Governance: An Analysis of Law No. 2/2002 - Setyorini, Fitri Adi; Umarach, Maretha Syawallin (Jurnal Ilmu Kepolisian, 2025)
This study analyzes Indonesia's domestic security paradigm through Law No. 2 of 2002 concerning the Indonesian National Police, applying realism, liberalism, and constructivism approaches. Using quantitative content analysis, the study evaluates themes such as actors, authority, budget, governance, and outputs within the law. The findings highlight a predominant focus on the realism approach, characterized by state-centric actors, regulation-driven governance, and outputs emphasizing law enforcement and public security. In contrast, liberal and constructivist perspectives, which prioritize non-state actors and community-oriented policies, are underrepresented. This gap underscores the challenges of balancing centralized authority with democratic principles and human rights. The study identifies potential risks, including militaristic tendencies and public distrust, stemming from this realist-heavy framework. It suggests reforms to integrate democratic governance and community engagement principles, fostering trust and collaboration between the police and the public. These insights contribute to broader discussions on security governance in transitioning democracies.